Imām Ibn Khuzaymah and His Methodology in Ṣaḥīḥ Ibn Khuzaymah - Mehmood, Sajid; Al Azhari, Muhammad Riaz Khan (Journal of Islamic and Religious Studies, 2016)
Qur’an and Prophetic traditions (Hadith) are the fundamental sources of Islam. Muslims believe that Qur’an is the word of God (Allah). Hadith (Prophet’s Sayings, actions and silent approval and disapproval for something) likewise is based on divine revelation. Qur’an affirms also this view: (God says) Your Companion (Muhammad) has neither gone astray nor has erred. Nor does He speak of (his own) desire. It is only a Revelation revealed. Al-Qur’an (53:2-4). Allah Almighty Himself took the responsibility to guard His word (the Qur’an): (He says :) verily, we, it is We Who have sent down the Dhikr (i.e. the Qur’an) and surely, We will got it (from corruption). (Al-Qur’an:15:9) on the contrary the responsibility to guard the prophetic traditions (Hadith) was put on the shoulders on the Muslim Ummah. The scholars of Islam (Ulamas) try their utmost to collect and save the Prophetic traditions and guard it from any alteration .To achieve this purpose, they introduced different hadith sciences to distinguished between the true and the fabricated hadith.The authentic Sunnah is contained within the vast body of Hadith literature. Different scholars have compiled the books which contain a large numbers of authentic Ahadith (Ahadith Sahiha), one of them is Imam Ibn e Khuzaima. In this article we will discuss the Imam Ibn e Khuzaima approach towards “Ahadith al Sahiha” in his book “Sahih Ibn e Khuzaima”.